Identification of Factors Involved in Neurogenesis Recovery After Irradiation of the Adult Mouse Subventricular Zone: A Preliminary Study - Chevalier, François; Chicheportiche, Alexandra; Daynac, Mathieu; Depagne, Jordane; Bertrand, Pascale; Boussin, François D.; Mouthon, Marc-André (IntechOpen, 2012)
None